Assessing the validity of stated preference data using follow-up questions (2017)
Stated preference (SP) studies such as contingent valuation (CV) and discrete choice experiments (DCEs) are often used to attempt measurement of willingness to pay (WTP) for environmental goods. However, concern exists that these methods do not provide data that can support valid, reliable, and meaningful WTP estimates, especially in the context of estimating non-use values for environmental goods. The foundation of all survey-based exercises is that the questions as asked by the researcher and answered by the respondent share a common understanding. This common understanding is difficult to achieve. In WTP studies, additional criteria must be met if the results are to provide data for estimating Hicksian welfare measures.2 The criteria that must be satisfied if SP data are to be theoretically interpreted via the standard microeconomic rational choice model (RCM) have been widely discussed in the literature (e.g., Mitchell and Carson, 1989; Carson and Groves, 2007; US EPA SAB, 2009; Carson and Louviere, 2011; Bateman, 2011). General consensus exists on these criteria: that the respondents believe the information in the survey and base their responses solely on outcomes described in the survey, they treat the exercise posed in the survey as they would a real decision that affects their budget, and they answer valuation questions as rational economic agents with well-defined preferences who are trading money for economic goods. One approach for assessing whether respondents satisfy these criteria is to use follow-up, debriefing questions. The earliest and most ubiquitous follow-up questions were “Yes/No” follow-ups based on recommendations from the National Oceanic and Atmospheric Administration (NOAA) Blue Ribbon Panel on contingent valuation. As part of a review of the use of contingent valuation to estimate lost non-use values in the context of natural resource damage assessments (NRDAs), the NOAA panel recommended the use of “Yes/No” follow-ups to determine the type of response (i.e., protest vote, yea-saying, etc.). However, the scope of follow-up questions has expanded over time (Krupnick and Adamowicz, 2006 provide a discussion). These questions may be used to “shore up the credibility of the survey” (ibid.), “to modify the estimate derived from one or more SP questions in some way” (Carson and Louviere, 2011), or to identify “problematic responses” in order to delete some responses or respondents or treat them as zeros for analysis purposes. Despite their ubiquity, there is little consistency to either the questions posed or their use to modify analyses. First, no consensus exists on what or how many questions to ask in order to identify problematic responses. Second, most studies report results by question rather than by respondent; thus, the literature does not evaluate how many respondents had a general understanding of the tasks asked of them. Third, other than those respondents who protest the SP exercise as a whole and typically are dropped from the analysis sample, no consensus exists on what to do about problematic answers. This lack of consistency in the use of follow-up questions is troubling, as substantial proportions of respondents may give problematic answers to some of the follow-up questions and welfare estimates may be sensitive to decisions made regarding such answers.